Stress fractures in elite male football players - Ekstrand, J.; Torstveit, M. K. (Scandinavian Journal of Medicine & Science in Sports, 2012)
The objective was to investigate the incidence, type and distribution of stress fractures in professional male football players. Fifty-four football teams, comprising 2379 players, were followed prospectively for 189 team seasons during the years 2001-2009. Team medical staff recorded individual player exposure and time-loss injuries. The first team squads of 24 clubs selected by UEFA as belonging to the 50 best European teams, 15 teams of the Swedish Super League and 15 teams playing their home matches on artificial turf pitches were included. In total, 51 stress fractures occurred during 1 180 000 h of exposure, giving an injury incidence of 0.04 injuries/1000 h. A team of 25 players can therefore expect one stress fracture every third season. All fractures affected the lower extremities and 78% the fifth metatarsal bone. Stress fractures to the fifth metatarsal bone, tibia or pelvis caused absences of 3-5 months. Twenty-nine percent of the stress fractures were re-injuries. Players that sustained stress fractures were significantly younger than those that did not. Stress fractures are rare in men's professional football but cause long absences. Younger age and intensive pre-season training appear to be risk factors.